MUSTAQIL TA’LIMNI TASHKIL ETISHNING PEDAGOGIK-PSIXOLOGIK JIHATLARI - Mamatova Sayyara Shavkatovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article examines the difficulties and problems in the process of organizing independent work, independent training of future engineers studying in the field of engineering education and professional, practical, technical and technological activities, independent learning, pedagogical and psychological aspects of organization, activation in the process of independent learning, the desire of students to independently acquire theoretical knowledge and practical skills is highlighted.